Efeitos cardiovascular e analgésico da metadona via intramuscular ou epidural em cadelas submetidas à mastectomia - Coradini, Gabriela Pesamosca (2016)
The objective of this study was to evaluate the cardiovascular effects and compare the analgesic efficacy intraoperative and postoperative provided by methadone administered via epidural (EP) or intramuscular (IM) in bitches submitted to total unilateral mastectomy surgery. For this it was used 12 female dogs anesthetized and randomly distributed into two groups of six animals each. In the first group the methadone was administered via epidural, after anesthetic stabilization (GEP) and another group, methadone was administered via intramuscular in the pre-anesthetic medication (GIM). In the first part of the study evaluated heart rate (HR), respiratory rate (RR), systolic blood pressure (SBP), mean arterial pressure (MAP), diastolic blood pressure (DBP), carbon dioxide released at the end of expiration (ETCO 2) and arterial blood gas analysis. Both FC when FR and blood gas analysis did not show significant changes. The GIM had higher values in all pressure ratings (DAP, MAP and SAP), but within the parameters for the species. The GIM had higher values in all pressure ratings (DAP, MAP and SAP), but within the range for the species. Both routes of administration showed little change in the evaluated parameters, however the epidural demonstrated greater anesthetic and analgesic stability for this procedure. In the second part of the study, the postoperative analgesia was measured by pain scales at the University of Melbourn, Visual Analogue Scale (VAS) and Glasgow Simplified Composed Measure pain scale. It also evaluated serum concentration of cortisol, lactate and glucose. Difference was observed between the groups only in the T6 Melbourn scale and analgesic rescue at T2 to the animals of the GIM. Cortisol presented a significant enhancement in the first hour in both groups and the remaining analyzes did not demonstrate differences. The administration of methadone epidural provided higher postoperative analgesia period that intramuscular administration showing to be the best option for this procedure. For both steps, the mean scores were submitted to statistical analysis by Kruskal-Wallis test to the groups between the different moments and Wilcoxon to compare the groups within each time. The Scott-Knott post-test was used for comparison in pairs at 5% significance level. After observing of the study in its two steps can be concluded that both methadone administered via epidural as intramuscular are secure in the perioperative period because does not cause significant changes in the physiological parameters. However the epidural proved to have a more efficient analgesia during surgery and post-operative period, in which we observed a greater analgesia period which makes it a safe and the best route for satisfactory analgesia in the procedure and in the studied species.